2021
DOI: 10.31557/apjcp.2021.22.12.3847
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Weight Loss on Patients with Locally Advanced Esophageal and Esophagogastric Junction Cancers Treated with Chemoradiotherapy

Abstract: Introduction: Malnutrition and weight loss are commonly observed in patient with esophageal and esophagogastric junction (EGJ) cancers. Chemoradiotherapy (CRT) is a mainstay of treatment for locally advanced esophageal and EGJ cancers. Impact of weight loss on patients with treated with CRT was not well studied. Methods: Patients with locally advanced esophageal and EGJ cancer who received CRT were identified in our institutional database and allocated into low (LWL) and high (HWL) weight loss groups. HWL was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Esophagectomy with lymphadenectomy and perioperative adjuvant therapy is the standard treatment for resectable esophageal cancer (3,4). Several prognostic factors for resectable esophageal cancer have been reported, including the perioperative nutritional status, metabolic function, and immunological function (5)(6)(7)(8)(9)(10). Among them, the liver function is one of the key prognostic factors (11)(12).…”
mentioning
confidence: 99%
“…Esophagectomy with lymphadenectomy and perioperative adjuvant therapy is the standard treatment for resectable esophageal cancer (3,4). Several prognostic factors for resectable esophageal cancer have been reported, including the perioperative nutritional status, metabolic function, and immunological function (5)(6)(7)(8)(9)(10). Among them, the liver function is one of the key prognostic factors (11)(12).…”
mentioning
confidence: 99%
“…To further determine the nutritional status of patients, a comprehensive and detailed nutritional assessment is required. As for weight loss, it has been found that excessive weight loss during NAT or after surgery is associated with severe postoperative complications and worse survival in multiple cancers ( 10 , 11 , 31 ). Nevertheless, weight is affected by many factors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, malnutrition is considered a risk factor for adverse clinical outcomes in multiple tumors ( 7 9 ). In patients with gastric cancer and AEG, those who were at nutritional risk as assessed by the Nutritional Risk Screening 2002 (NRS 2002) and experienced weight loss, had more severe postoperative complications and poorer survival ( 7 , 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to determine prognostic factors and to establish which patients with prognostic factors require more aggressive treatment. Perioperative systemic inflammation is associated with both short-and long-term oncological outcomes (7,8). Previous studies demonstrated that perioperative systemic inflammation accelerated tumor invasion and enhanced micrometastasis in various malignancies (9,10).…”
mentioning
confidence: 99%